Whole body PET/CT in the follow-up of asymptomatic patients with stage IIB-IIIB cutaneous melanoma*. (1st November 2016) - Koskivuo, I.; Kemppainen, J.; Giordano, S.; Seppänen, M.; Veräjänkorva, E.; Vihinen, P.; Minn, H.
Abstract: Background: Whole body positron emission tomography (PET)/computed tomography (CT) is a sensitive imaging technique in patients with metastatic melanoma, but its role in the follow-up of asymptomatic high-risk patients is unclear. The aim was to study the role of PET/CT as a routine surveillance imaging tool in asymptomatic high-risk patients at the early stage of follow-up combined with a sufficient follow-up over several years. Material and methods: A total of 110 asymptomatic patients with clinically local American Joint Committee on Cancer (AJCC) stage IIB-IIIB melanoma underwent routine whole body PET/CT scanning after a mean interval of seven months after initial surgery. Clinical data were retrospectively analyzed after a median follow-up time of 4.6 years. Results: Recurrent melanoma was detected in 45 patients (41%) and 36 (33%) died of melanoma. In 11 asymptomatic patients (10%) occult disease was detected with a single PET/CT. In seven of these patients (64%), positive PET/CT finding had major influence in treatment decisions. Four patients underwent surgical metastasectomy and two of them remained disease-free. In 34 patients (31%) PET/CT revealed no disease, but recurrence was detected at a median time of 19 months after negative PET/CT scan. In 50 patients (45%) PET/CT finding was true negative. In 15 patients (14%) scan was false positive leading to additional management or repetitive imagings. Conclusion: A single PET/CT could detect 24% of all recurrences in asymptomatic melanoma patients at the early stage of follow-up, but an earlier detection of occult metastases did not improve survival.